Methodological insights into the study of centuriated field systems: a landscape archaeology perspective - Orengo, Hèctor A.; Palet Martínez, Josep M. (Fabrizio Serra editore, 2009)
The morphological identification of centuriated field systems has been characterised from its beginnings by methodological approaches mainly sustained on actus-based modular relationships and orientations. Many researchers dedicated to the identification of centuriations have only performed archaemorphological analyses based on interpretation of aerial photographs and maps without field verification or any other proof of the validity of their hypothsis. Their restitutions consisted of a set of lines over a map or an aerial photograph which often lacked precision and spatial resolution. This article argues that the study of centuriations should transform its aims, scope and methodologies to be converged with those presented by diachronic transdisciplinary landscape archaeology. In order to do so a series of integrated methodological approaches are exposed and their applicability discussed.